IJCM_67A: Unmet need for family planning and the factors affecting it in rural area of Udupi district, Karnataka - Jay Ratna; Kini Sanjay; Alok Yash; Kunder Manjula Anil (Wolters Kluwer Medknow Publications, 2024)
Background: The world population is expected to increase from 8 billion currently to 9.7 billion in 2050. China (1.4 billion) and India (1.4 billion) remain the two most populous countries of the world representing 18 percent of the world's population respectively. Unmet need for contraception and unintended pregnancy are important public health concerns for India in this context. Objectives: 1. To estimate the prevalence of unmet need for family planning among eligible couples. 2. To assess the knowledge and attitude towards contraceptive usage among the eligible couples Methodology: After obtaining the approval of institutional ethics committee, a cross sectional study was conducted in Shirva, a rural area of Udupi district, Karnataka. List of eligible couples residing in areas coming under the sub centres of CHC Shirva which is a field practice area of the Department of Community Medicine, KMC, Manipal was obtained. Married women of the age group 18-49 years who are were included in the study. Data was collected by personal interviews using a semi structured, pre -designed, pre-tested questionnaire. Data was analyzed using SPSS version 26. Regression analyses was performed to find out the independent effect of various factors. Results: From the preliminary analysis of 539 participants, the unmet need for family planning was found to be 43.4%. The mean age was found to be 33.68 with a standard deviation of 6.27. The mean age at marriage and the mean age at birth of first child were found to be 22.40 and 22.97 respectively. Most of participants belonged to Hindu religion (57%), followed by Muslims (38.2%) and Christians (4.6%). 36.7% were educated up to secondary school and 21.3% up to graduation and above. Conclusion: From this study, the unmet need for family planning was found to be high.